2020
DOI: 10.1038/s41598-020-67514-4
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the antifibrotic effect of the antiparasitic drug Praziquantel in in vitro and in vivo preclinical models

Abstract: Tissue fibrosis underlies the majority of human mortality to date with close to half of all reported deaths having a fibrotic etiology. The progression of fibrosis is very complex and reputed irreversible once established. Although some preventive options are being reported, therapeutic options are still scarce and in very high demand, given the rise of diseases linked to fibroproliferative disorders. Our work explored four platforms, complementarily, in order to screen preventive and therapeutic potentials of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 65 publications
0
20
0
Order By: Relevance
“…PZQ treatment decreases the number of hepatic eggs and therefore leads to a decrease in granuloma and fibrotic tissue formation. However, PZQ has only a little or no effect on the already established fibrotic tissues and is therefore not beneficial for patients in the later stage of schistosomiasis [ 84 , 86 ]. Sch B, in addition to the anti-parasitic effects shown in this study, can also reverse the existing fibrosis [ 25 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PZQ treatment decreases the number of hepatic eggs and therefore leads to a decrease in granuloma and fibrotic tissue formation. However, PZQ has only a little or no effect on the already established fibrotic tissues and is therefore not beneficial for patients in the later stage of schistosomiasis [ 84 , 86 ]. Sch B, in addition to the anti-parasitic effects shown in this study, can also reverse the existing fibrosis [ 25 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although some study suggested that the persistent use of PZQ may also provide an antifibrotic effect against schistosomiasis [82][83][84], this beneficial effect usually occurs at an earlier stage [84][85][86]. PZQ treatment decreases the number of hepatic eggs and therefore leads to a decrease in granuloma and fibrotic tissue formation.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…The volume of administration to mice was 200 µL. S. mansoni-infected mice were administered by oral gavage twice during week 6 post infection for deparasitization, as previously optimized in mice (14). Deparasitized animals were further subjected or not to cycles of reinfection and deparasitization with PZQ up to a maximum total of 3 infection cycles for some animals.…”
Section: Preparation Of Pzq Solution and Administration Schemesmentioning
confidence: 99%
“…The upper aqueous serum phase was aliquoted into tubes and stored at -80°C until further use. Livers were excised then approximately one-quarter of each liver was used for cell isolation and flow cytometric analyses as previously described (14,15), another quarter was stored in formalin for histology, a quarter used for egg count and the last quarter used to estimate the relative tissue cytokine contents as a proxy for the local response elicited by trapped parasite eggs.…”
Section: Sampling (Liver Serum)mentioning
confidence: 99%
“…It is a broadspectrum drug used to treat many parasitic infections, including cysticercosis, tapeworm disease, and clonorchiasis (Zhang et al, 2020). Praziquantel is considered a relatively low-toxic drug that does not possess embryotoxic, mutagenic, and teratogenic properties and does not affect the postnatal development of the body (Demidov, 1982;Engasheva, 2011;Garcia et al, 2011;Zolotareva and Zeynalov, 2015;Harvie et al, 2019;Liu et al, 2019;Nono et al, 2020). At the same time, with all the listed advantages, praziquantel has several disadvantages: 1) low solubility in water and, as a result, limited bioavailability of this substance in liquid compositions; 2) lack of the necessary activity concerning the roundworms; 3) the lack of complete clearance of praziquantel from the body, which, with prolonged use, can lead to increased toxicity to animals; 4) pronounced bitter taste, which is a significant obstacle in the development of medicinal products for oral administration and, in particular, their liquid forms intended for dogs and cats (Subbotin et al, 2000;Xu et al, 2009;Sousa-Figueiredo et al, 2012;Zolotareva and Zeynalov, 2015).…”
Section: Introductionmentioning
confidence: 99%